Distinct asthma phenotypes among older adults with asthma - Baptist, Alan P. (J Allergy Clin Immunol Pract, 2017)
BACKGROUND: Older adults have high rates of asthma morbidity and mortality. Asthma is now recognized as a heterogeneous disease, yet the distinct phenotypes among older adults are unknown. OBJECTIVE: To identify asthma phenotypes in a diverse population of elderly asthma patients. METHODS: Using cluster analysis, 180 older adults with persistent asthma were analyzed. Subjects completed detailed questionnaires, skin prick testing, and spirometry with reversibility. Twenty-four core variables were analyzed. RESULTS: Four groups were identified. Subjects in Cluster 1 (n = 69) typically had asthma diagnosed after the age of 40 and the shortest duration of asthma. Cluster 2 (n = 40) had the mildest asthma defined by spirometry, asthma control (ACT), and asthma quality of life (AQLQ). They also had the lowest BMI, lowest depression score, and least number of co-morbidities. Cluster 3 (n = 46) had the longest duration of asthma (56 years) and the highest atopic skin test sensitization (74%). Cluster 4 (n = 25) had the most severe asthma, with extremely low FEV1 % predicted (37.8%), lowest ACT and lowest AQLQ scores. They were more likely to be black and had the highest co-morbidities. Using BMI, post-treatment FEV1% predicted, and duration of asthma, 95.6% of subjects were able to be correctly classified. CONCLUSION: In older adults with asthma, distinct phenotypes vary on key features that are more pronounced among the elderly, including comorbidities, fixed airway obstruction, and duration of asthma > 40 years. Further work is required to determine the clinical and therapeutic implications for different asthma phenotypes in older adults.